2005
DOI: 10.1074/jbc.m408850200
|View full text |Cite
|
Sign up to set email alerts
|

CIL-102 Interacts with Microtubule Polymerization and Causes Mitotic Arrest following Apoptosis in the Human Prostate Cancer PC-3 Cell Line

Abstract: There have been no therapeutic agents that provide a survival advantage in hormone-refractory prostate cancer. Recently, the Food and Drug Administration approved docetaxel combined with prednisone for the treatment of patients with advanced metastatic prostate cancer, and it does show a survival benefit. Hence, anti-microtubule drugs might be of benefit in chemotherapy of hormone-refractory prostate cancer. We used metastatic hormone-refractory prostate cancer PC-3 cells to investigate potential molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…Representative of four independent experiments. the antimitotic agents (25,26). In addition, the CHM-1-induced activation of Cdc2 kinase activity, the elevation of MPM2 phosphoepitopes, and the inhibition of cell growth were all attenuated by roscovitine.…”
Section: Discussionmentioning
confidence: 90%
“…Representative of four independent experiments. the antimitotic agents (25,26). In addition, the CHM-1-induced activation of Cdc2 kinase activity, the elevation of MPM2 phosphoepitopes, and the inhibition of cell growth were all attenuated by roscovitine.…”
Section: Discussionmentioning
confidence: 90%
“…Dictamnine (Dic), a natural alkaloid, was isolated from the root of Dictamnus dasycarpus Turcz, and has been reported to possess anti-platelet aggregation, fungal activity and vascular-relaxing effects (Huang et al, 2005;Huang et al, 2007;Guo et al, 2008). Recently, it was reported that Dic could induce cytotoxicity in human cervix, colon, and oral carcinoma cells (Huang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that Dic could induce cytotoxicity in human cervix, colon, and oral carcinoma cells (Huang et al, 2005). In addition, derivatives from Dic have been exhibited anticancer activity (Huang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The analytic method was modified from the previous description (12). In brief, cells were incubated with anti-p65 antibody at 37jC for 45 minutes and stained with FITC-conjugated antirabbit IgG antibody plus 1 Ag/mL 4V,6-diamidino-2-phenylindole in PBS for 30 minutes at room temperature.…”
Section: Cell Culturementioning
confidence: 99%
“…Total cell lysate was lysed with lysis buffer as previously described (12). The nuclear protein fractions were separated as described previously (14).…”
Section: Western Blottingmentioning
confidence: 99%